Internet of Things integrated with solar energy applications: a state-of-the-art review - Nath D.C.; Kundu I.; Sharma A.; Shivhare P.; Afzal A.; Soudagar M.E.M.; Park S.G. (Springer Science and Business Media B.V., 2025)
Numerous investigations and research projects carried out over the past several years in a wide range of application domains have revealed the potential of IoT (Internet of Things). Solar energy is a renewable source of energy and a sustainable foundation for human civilization; thus, the use of IoT with solar energy-powered devices has definitely been a revolutionary reformation in technology. Researchers have looked into ways to use IoT to change the network structure by recognizing different ecosystem components for intelligent solar-powered city control. Furthermore, countless studies have been made on solar monitoring and solar tracking systems using different IoT technologies in order to target better efficiency, automated control, and monitoring, maximum energy generation etc. The contribution of this study is to make aware everyone about the integration of the renewable energy with the revolution 4.0 which is the major primary topic of the current technology nowadays. Also, the major projects like smart city are being pursued in many developing countries like India and so concepts like IoT are mandatory for these major projects. Also, the solar panel efficiency may be increased and maintenance expenses decreased with the help of the Internet of Things in monitoring and optimizing the panels. As this technology may aid in managing energy usage in real time, solar power can be more consistent and adaptable to fluctuating demand. This article provides a state-of-the-art review of the application of IoT in effective solar energy utilization. The use of IoT in solar energy tracking, power point tracking, energy harvesting, smart lighting system, PV panels, smart irrigation system, solar inverters, etc., is reviewed. Hence, by merging solar power with the Internet of Things, we can provide companies and households with long-term, affordable energy solutions that help encourage responsible expansion and a better future. The outcome of this study reveals that IoT is very much successful in providing smart and efficient solar energy output from countless devices. A vast scope of work and research on IoT applications for smart solar energy utilization still exists in the future. ? The Author(s), under exclusive licence to Springer Nature B.V. 2023.